Treatment for upper esophageal sphincter dysfunction in a patient with poststroke dysphagia: A case report. Issue 13 (March 2019) - Wei, Pengxu; Xu, Yafei; Zhang, Zuting; Zhang, Simin; Lv, Zeping
Abstract: Rationale: Botulinum toxin injection is a widely used procedure for the treatment of the dysfunction of the upper esophageal sphincter (UES). Although the injection can be guided by ultrasound, electromyography, or computed tomography, such techniques cannot determine the exact extent of narrowed UES and ensure that the narrowed extent is fully covered by the treatment. This report describes a dual guiding technique with ultrasound and the balloon catheter in a patient with poststroke dysphagia to improve these weaknesses. Patient concerns: The patient was admitted to a rehabilitation hospital 2 weeks postcerebral infarction. Diagnoses: Clinical presentation of the patient included severe hemiplegia and dysphagia. The fiberoptic endoscopic evaluation of swallowing (FEES) revealed penetration/aspiration when swallowing 1 ml water and 1 ml yogurt and pooling in the postcricoid region. Interventions: Balloon catheter dilatation procedures and Botulinum toxin injection were performed. We used a dual guiding technique with ultrasound and the balloon catheter to determine the whole segment of UES dysfunction by locating the lowest level of the impaired UES opening and to reduce difficulty in differentiating UES from adjacent tissues during Botulinum toxin injection. Outcomes: No persistent progress was observed on the symptoms and volume of the balloon during dilatation. The patient showed quick responses after Botulinum toxin injection. The postinjection balloon catheter dilatation showed an increased maximum volume (preinjection, 5.5 ml vs. postinjection, 14 ml), and the patient was able to eat yogurt, congee, or semi-solid food 100–150 ml 4 weeks after the injection. Lessons: The dual guiding method holds several advantages, suggesting that it may be considered as a promising choice in dealing with UES dysfunction. Abstract : Supplemental Digital Content is available in the text